Leonard C. Sebastian, Syaq Hasyim and Alexander R. Arifianto (eds.) (2021). Rising Islamic Conservatism in Indonesia Islamic Groups and Identity Politics. London & New York: Routledge. 230 Pages. ISBN: 978-1-003-01092-0 - Zulfadli, Zulfadli (Journal of Al-Tamaddun, 2023)
The rise of Islamic conservatism in post-New Order Indonesia is related to strengthening religious attitudes and understandings in religion. However, it has several socio-economic, political, theological implications and significant challenges to democracy and diversity in Indonesia. The presence of Islamic conservatism groups and the development of identity politics have resulted in the religious conservatism movement having a significant influence on society. This book is the latest study explaining Islamic conservatism, focusing on discussing Islamic groups and identity politics at the national, regional, and local levels. Conservative groups use religion as a vehicle in expressing their identity and respond to social, political, and economic issues as part of their political aspirations. The activities of Islamic conservatism groups have changed the face of Indonesian Islam from an inclusive-moderate pattern to an exclusive-literal orientation.